2016
DOI: 10.1016/j.humimm.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

The immunosuppressive effect of domain-deleted dimer of HLA-G2 isoform in collagen-induced arthritis mice

Abstract: 28HLA-G is involved in maternal-fetal immune tolerance and is reported to be a natural 29 tolerogenic molecule. Seven-spliced isoforms including dimeric and β2m-free forms 30 have been identified. The major isoform, HLA-G1 (and its soluble type HLA-G5), binds

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…In this study, we prepared functional rHLA-G2, which exhibited specific binding to LILRB2 in vitro ( Fig. 3) and an antiinflammatory effect in vivo (8). Furthermore, the EM structure of HLA-G2 is in good agreement with the fit for the HLA-G1 a1 and a3 domains without the Cys 42 -Cys 42 disulfide bond.…”
Section: Hla-g2 Proteins Bind To Lilrb2 With a Notable Avidity Effectmentioning
confidence: 55%
See 2 more Smart Citations
“…In this study, we prepared functional rHLA-G2, which exhibited specific binding to LILRB2 in vitro ( Fig. 3) and an antiinflammatory effect in vivo (8). Furthermore, the EM structure of HLA-G2 is in good agreement with the fit for the HLA-G1 a1 and a3 domains without the Cys 42 -Cys 42 disulfide bond.…”
Section: Hla-g2 Proteins Bind To Lilrb2 With a Notable Avidity Effectmentioning
confidence: 55%
“…This is supported by the observations of the existence of healthy individuals who do not have HLA-G1 and who, therefore, would be predicted only to have HLA-G2 forms capable of binding to LILRB2. In a previous study, we demonstrated the significant immunosuppressive effects of the HLA-G1 monomer/homodimer and HLA-G2 in a CIA mice model (3,8). In terms of receptor distribution, paired Ig-like receptor B (mouse) and LILRB2 FIGURE 3.…”
Section: Hla-g2 Proteins Bind To Lilrb2 With a Notable Avidity Effectmentioning
confidence: 93%
See 1 more Smart Citation
“…Notably, the amounts of HLA-G inversely correlate with the severity of autoimmune diseases [5,6,7]. We also demonstrated that the administration of the HLA-G molecule improved the symptoms of the collagen induced arthritis model mice and the atopic dermatitis model mice [8,9,10]. Furthermore, certain tumor cells also express HLA-G on the surface to suppress immune activation and escape immune surveillance [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, some researchers demonstrated that LILRB family genes could bind with MHC class I and β2m [21]. As predicted, GFP-linked LILRB1 and LILRB3 showed a strikingly different pattern of gene expression compared with GFP alone.…”
Section: Resultsmentioning
confidence: 68%